Rewriting the intersex body: On the opera adaptation of Herculine Barbin’s Memoirs - Gonzalo Iturregui-Gallardo (JoSTrans: The Journal of Specialised Translation)
Herculine Barbin’s memoirs, published by Foucault in 1978, are considered the first testimony of an intersex person. Barbin’s story has been adapted several times, including in a 19th-century German short story and in a 1985 French film. In addition, the translation of the memoirs has been analysed from queer perspectives (Rose, 2021) due to the protagonist’s gender undecidability. This undecidability surfaces not only in translation but also in the memoir’s audiovisual rewritings, including most recently, the opera Alexina B. (García-Tomás, 2023) which premiered in Barcelona. This paper analyses the rewriting process in this multimodal (textual/audiovisual) and intralinguistic (French) translation/adaptation. Alexina B. was created after a research process not only on the historical character, but also on the (historical) intersex experience. This article’s analytical framework is based on queer and feminist approaches applied to Translation Studies, and on the notions of rewriting and translation as adaptation, practices through which the ethos is reworked (Spoturno, 2022). This framework serves to analyse the different adaptations (story, film and opera) and to argue that the opera presents a more queer-conscious narrative and a character who, despite being a victim of the social constraints of her time, was also master of her non-normative sexuality and desire.